Connective tissue growth factor and β‐catenin constitute an autocrine loop for activation in rat sarcomatoid mesothelioma. Issue 4 (16th June 2014) - Jiang, Li; Yamashita, Yoriko; Chew, Shan‐Hwu; Akatsuka, Shinya; Ukai, Shun; Wang, Shenqi; Nagai, Hirotaka; Okazaki, Yasumasa; Takahashi, Takashi; Toyokuni, Shinya
Abstract Due to the formerly widespread use of asbestos, malignant mesothelioma (MM) is increasingly frequent worldwide. MM is classified into epithelioid (EM), sarcomatoid (SM), and biphasic subtypes. SM is less common than EM but is recognized as the most aggressive type of MM, and these patients have a poor prognosis. To identify genes responsible for the aggressiveness of SM, we induced EM and SM in rats, using asbestos, and compared their transcriptomes. Based on the results, we focused on connective tissue growth factor (Ctgf), whose expression was significantly increased in SM compared with EM; EM itself exhibited an increased expression of Ctgf compared with normal mesothelium. Particularly in SM, Ctgf was a major regulator of MM proliferation and invasion through activation of the β‐catenin–TCF–LEF signalling pathway, which is autocrine and formed a positive feedback loop via LRP6 as a receptor for secreted Ctgf. High Ctgf expression also played a role in the epithelial–mesenchymal transition in MM. Furthermore, Ctgf is a novel serum biomarker for both early diagnosis and determining the MM prognosis in rats. These data link Ctgf to SM through the LRP6–GSK3β–β‐catenin–TCF–Ctgf autocrine axis and suggest Ctgf as a therapeutic target. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.